(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In the article, the construction of industrial enterprises in Uzbekistan ensures the employment of the population, but the imbalances between industrial enterprises and housing in their protection systems, the environmental situation and economic crises caused by the adverse effects of industrial enterprises on water, soil, and atmosphere are highlighted based on archival sources. Development of mineral fertilizers production and chemical industry enterprises connected with cotton cultivation in agriculture, increase of cotton yield, but negative consequences caused by chemicalization are described.